GUIDING AND PREPARING HIGH SCHOOL STUDENTS FOR SUCCESSFUL UNIVERSITY EDUCATION - Ebrahim, Husain Abduljalil (IJRDO- Journal of Educational Research, 2018)
The transition process of high school students to university education and college life is quite challenging. Therefore, this process should not be unguided, as this research paper suggests, in order to equip the high school students with the necessary skills and background to enable them to go through this phase successfully. There should thus be a strategy or programme for the teachers and the administrative staff to be implemented in the high schools- to achieve this goal.However, this research paper was conducted to first find out whether the high schools are following any strategy or programme, evaluate the current programmes if they already exist and gauge the willingness of the schools, teachers and administrative staff to be a part of such strategies and programmes. Based on the result of this study, it was found that most of the schools with their academic and non-academic staff are not actually a part of a current strategy, but yet have the willingness to participate in any well-planned and feasible one.Thus, the study finally recommends that a specific strategy and programme should be formed and introduced to high schools in the Kingdom of Bahrain, mainly private schools until it is possible to access the public ones when the permission could be obtained.